Superalloys 2008 (Eleventh International Symposium) 2008
DOI: 10.7449/2008/superalloys_2008_63_72
|View full text |Cite
|
Sign up to set email alerts
|

The Microstructure and Mechanical Properties of EP741NP Powder Metallurgy Disc Material

Abstract: An effort to study the heat treatment methods and resultant mechanical properties of Russian powder metallurgy (P/M) alloy EP741NP has been undertaken. This effort has involved the detailed assessment of microstructures and mechanical properties from a sample of a production turbine engine disc as well as the manufacture, processing and characterization of two developmental lots of P/M EP741NP material processed by atomization, extrusion, isothermal forging and heat treating. The effects of processing and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Along the boundaries of the observed primary grains, there are overgrown precipitates of the γ' phase and carbide precipitates preventing grain growth and high-temperature creep. The microanalysis of the chemical composition of the tested material corresponds to the Russian EP741NP superalloy used for the construction of turbine discs in high-load turbine jet engines [12]. In order to unambiguously link the observed fatigue damage of the turbine disc material to the grain structure of the alloy used, microscopic observations were carried out, which clearly demonstrated that the material from which the turbine disc was made had a grain structure typical of the heat-resistant nickel superalloy produced using the powder metallurgy process.…”
Section: (C)mentioning
confidence: 99%
See 1 more Smart Citation
“…Along the boundaries of the observed primary grains, there are overgrown precipitates of the γ' phase and carbide precipitates preventing grain growth and high-temperature creep. The microanalysis of the chemical composition of the tested material corresponds to the Russian EP741NP superalloy used for the construction of turbine discs in high-load turbine jet engines [12]. In order to unambiguously link the observed fatigue damage of the turbine disc material to the grain structure of the alloy used, microscopic observations were carried out, which clearly demonstrated that the material from which the turbine disc was made had a grain structure typical of the heat-resistant nickel superalloy produced using the powder metallurgy process.…”
Section: (C)mentioning
confidence: 99%
“…Along the boundaries of the observed primary grains, there are overgrown precipitates of the γ' phase and carbide precipitates preventing grain growth and hightemperature creep. The microanalysis of the chemical composition of the tested material corresponds to the Russian EP741NP superalloy used for the construction of turbine discs in high-load turbine jet engines [12].…”
Section: (C)mentioning
confidence: 99%
“…[12,179] Highperformance gas turbine engines require PM superalloys, such as EP741NP developed in Russia, with low C contents and additional carbide or oxide formers instead. [180][181][182] Table 1, Table 3, and Table 5 highlight the unique properties of B, C, and Zr in GB segregation and precipitation. However, information on the combined impact of microalloying elements on the mechanical properties of Ni-based superalloys is more sparse.…”
Section: Solid-state Microsegregationmentioning
confidence: 99%
“…[ 12,179 ] High‐performance gas turbine engines require PM superalloys, such as EP741NP developed in Russia, with low C contents and additional carbide or oxide formers instead. [ 180–182 ]…”
Section: Combined Impacts Of Boron Carbon and Zirconiummentioning
confidence: 99%
“…Fig 6. Changes of of Al and Hf amount (mass fraction of total alloy) in γ phase with Hf content in FGH97 alloy…”
mentioning
confidence: 97%